1999
DOI: 10.1021/jm991035g
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2-Phenylimidazo[1,2-a]pyridine Derivatives as Potent and Selective Ligands for Peripheral Benzodiazepine Receptors:  Synthesis, Binding Affinity, and in Vivo Studies

Abstract: The substituent effects at positions 6 and 8 (compounds 17-31) as well as at the amide nitrogen (compounds 32-40) of a series of 2-phenylimidazo[1,2-a]pyridineacetamides were evaluated at both central (CBR) and peripheral (PBR) benzodiazepine receptors. The structure-activity relationship studies detailed herein indicate the key structural features required for high affinity and selectivity for PBR. Substitution on the imidazopyridine nucleus at position 8 with lipophilic substituents and the presence of one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 22 publications
4
81
0
1
Order By: Relevance
“…The possibility to increase the synthesis of neuroactive steroids has stimulated recent efforts to develop new more selective and efficient MBR ligands. Thus, derivatives of 2-phenyl-imidazol[1,2]pyrimidine bind MBR ligands with great affinity and selectivity, and when injected intraperitoneally, they significantly increase brain neurosteroid levels in castrated and adrenalectomized rats, in agreement with a stimulatory effect on brain neurosteroidogenesis Trapani et al, 1999). Among the pharmaceutical agents that have been recently developed to influence neurosteroid levels in the brain are the steroid sulfatase inhibitors.…”
Section: Discussionmentioning
confidence: 91%
“…The possibility to increase the synthesis of neuroactive steroids has stimulated recent efforts to develop new more selective and efficient MBR ligands. Thus, derivatives of 2-phenyl-imidazol[1,2]pyrimidine bind MBR ligands with great affinity and selectivity, and when injected intraperitoneally, they significantly increase brain neurosteroid levels in castrated and adrenalectomized rats, in agreement with a stimulatory effect on brain neurosteroidogenesis Trapani et al, 1999). Among the pharmaceutical agents that have been recently developed to influence neurosteroid levels in the brain are the steroid sulfatase inhibitors.…”
Section: Discussionmentioning
confidence: 91%
“…Based on results from radioligand binding assays, it was shown that disubstitution at 6-and 8-positions on the pyridine moiety with dichloro, dibromo, 6-CF 3 /8-chloro, 6-bromo/8-CH 3 or 6-CH 3 /8-Br substituents was a core feature in promoting selectivity for the PBR. Further SAR and structure-selectivity relationship (SSR) research helped explore the effects of modifying the alkyl groups attached to the amide functionality and resulted in the synthesis of an extended series of 2-phenyl-imidazo[1,2-a]-pyridine derivatives [66]. In 1999, three lead compounds from this series, (CB 54), were investigated for their agonistic effect on brain and plasma neurosteroid concentrations in normal and adrenalectomized-orchiectomized (ADX-ORX) rats [67].…”
Section: Phenoxyphenyl-acetamide Derivativesmentioning
confidence: 99%
“…Autoradiographic and biochemical studies revealed that the highest density binding of [ 3 H]DAA1106 in the brain was in the olfactory bulb, followed by the cerebellum and cerebral cortex [68]. [2-(4-chlorophenyl)imidazo [1,2-a]pyridin-3-yl)]acetamide, although displaying high PBR affinity (5-10 nM), was the only reported 2-phenyl-imidazo[1,2-a]-pyridine that failed to have any effect on neuroactive steroid concentration in cerebral cortex and is thus considered to be an antagonist [66]. These results proved that there was no direct association between affinity and selectivity for the PBR and functional steroidogenic activity.…”
Section: Phenoxyphenyl-acetamide Derivativesmentioning
confidence: 99%
“…The anesthetized animals were decapitated and the brain cortex, characterized by high BDR content, was rapidly removed in the cold. The analysis of the interaction of 1-17 with CBDR and PBDR was carried out according to previous procedures [17,18]. The affinity was found relative to the compounds at 1 µM to remove radioligands from sites of their specific binding with receptors.…”
Section: Methodsmentioning
confidence: 99%